Endoscopic Findings of Mucosal Pemphigus Vulgaris: Clinical Correlation and Diagnostic Value - Zeynep Karaca Ural; Merve Hatun Erkayman; Zeynep Utlu; Handan Bilen; Özgür Yörük (Dermatology Practical & Conceptual)
Background: Pemphigus vulgaris (PV) is an autoimmune bullous disease that usually starts on the oral mucosa but it can affect all mucosal surfaces. There is limited data about endoscopic otorhinolaryngological examination of patients with PV.